2017
DOI: 10.3390/ijerph14040365
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Position and Suicidal Ideation in Men

Abstract: People in low socio-economic positions are over-represented in suicide statistics and are at heightened risk for non-fatal suicidal thoughts and behaviours. Few studies have tried to tease out the relationship between individual-level and area-level socio-economic position, however. We used data from Ten to Men (the Australian Longitudinal Study on Male Health) to investigate the relationship between individual-level and area-level socio-economic position and suicidal thinking in 12,090 men. We used a measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
3
13
1
Order By: Relevance
“…Similarly, we found that female gender was independently associated with 1.69-fold increase in risk of lifetime suicidal ideation in MMT patients. Consistent with the elevated risk of suicidal behaviors in individuals with low socio-economic status [ 28 , 29 ], we found that a low level of education and poor economic status were independent predictors of suicidal ideation. These associations might be explained by low socioeconomic status’ negative effects on health and wellbeing, which, in turn, place individuals at increased risk for suicidal behaviors.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, we found that female gender was independently associated with 1.69-fold increase in risk of lifetime suicidal ideation in MMT patients. Consistent with the elevated risk of suicidal behaviors in individuals with low socio-economic status [ 28 , 29 ], we found that a low level of education and poor economic status were independent predictors of suicidal ideation. These associations might be explained by low socioeconomic status’ negative effects on health and wellbeing, which, in turn, place individuals at increased risk for suicidal behaviors.…”
Section: Discussionsupporting
confidence: 83%
“…For suicide, the risk among men was the highest in the lowest skill-level occupations, whereas the analysis for women did not show as clear pattern, possibly partly due to power limitations. These findings agree with those from prior studies (Milner et al, 2013;Pirkis et al, 2017). Some characteristics of instrumentality, including denial of weakness or vulnerability and dismissal of need for help, may be more common among the low vs. high-skilled occupations, and contribute to the findings for men.…”
Section: Occupations and Mental Ill-healthsupporting
confidence: 92%
“…Some characteristics of instrumentality, including denial of weakness or vulnerability and dismissal of need for help, may be more common among the low vs. high-skilled occupations, and contribute to the findings for men. It has also been suggested that the elevated risk in the low-skilled occupations may derive from powerlessness, frustration and disrespect (Pirkis et al, 2017), or poorer overall socioeconomic circumstances (Roberts et al, 2013). However, in our data this association remained even after adjusting for income.…”
Section: Occupations and Mental Ill-healthcontrasting
confidence: 77%
“…Intermediary determinants comprise material circumstances, psychosocial processes and behaviours and biological factors [23]. Many studies have assessed the intermediary determinants of health in relation to social positions of gender or social class [24,25], but less so their contribution to intersectional inequalities in health. A Spanish example demonstrates contribution of intermediary determinants, including material factors, on the intersection between gender and social class and its effects on SRH [26].…”
Section: Introductionmentioning
confidence: 99%